2017
DOI: 10.1177/1740774517725289
|View full text |Cite
|
Sign up to set email alerts
|

Design of a randomized clinical trial of a colorectal cancer screening decision aid to promote appropriate screening in community-dwelling older adults

Abstract: We designed a randomized clinical trial to test a novel use of a patient decision aid to promote appropriate colorectal cancer screening and have recruited a diverse study population that seems similar between the intervention and control groups. The study should be able to determine the ability of a patient decision aid to increase individualized and appropriate colorectal cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Commensurate with previous reviews on this topic [ 6 , 7 ], a majority of articles analyzed reported improvement in practitioner performance [ 16 - 18 , 21 , 23 - 25 , 28 - 31 , 33 - 35 , 37 , 38 , 40 , 44 , 45 , 47 - 50 ], but contrary to the previous reviews, our review found articles that reported patient outcomes, and a majority were positive outcomes [ 15 , 17 , 20 , 21 , 23 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 , 41 - 48 , 50 ]. Although 9 articles did not discuss practitioner performance [ 15 , 20 , 26 , 27 , 32 , 39 , 41 , 43 ], only 5 articles reported no difference in productivity [ 19 , 22 , 36 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Commensurate with previous reviews on this topic [ 6 , 7 ], a majority of articles analyzed reported improvement in practitioner performance [ 16 - 18 , 21 , 23 - 25 , 28 - 31 , 33 - 35 , 37 , 38 , 40 , 44 , 45 , 47 - 50 ], but contrary to the previous reviews, our review found articles that reported patient outcomes, and a majority were positive outcomes [ 15 , 17 , 20 , 21 , 23 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 , 41 - 48 , 50 ]. Although 9 articles did not discuss practitioner performance [ 15 , 20 , 26 , 27 , 32 , 39 , 41 , 43 ], only 5 articles reported no difference in productivity [ 19 , 22 , 36 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 62%
“…Overall , the research generally supports the efficiency of CDSS technologies for practitioner performance [ 16 - 18 , 21 , 23 - 25 , 28 - 31 , 33 - 35 , 37 , 38 , 40 , 44 , 45 , 47 - 50 ] and effectiveness in patient medical outcomes [ 15 , 17 , 20 , 21 , 23 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 , 41 - 48 , 50 ]; however, a further in-depth review of their effectiveness, in particular for aspects such as the avoidance of alert fatigue and extension of CDSS utility, is important. Decision-support tools extend beyond the practitioner to the patient, and some tools are not software-based but based on patient-reported data [ 46 ].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Of those that identified performance, 82% (14/17) identified positive effect on practitioner performance as a result of using CDSS. Ten articles (37%) did not discuss practitioner performance (16,17,(20)(21)(22)24,26,30,32,34).…”
Section: Table 2: Summary Of Themes Identified For Practitioner Perfomentioning
confidence: 99%